Phylogenetic and Mutation Analysis of Hemagglutinin Gene from Highly Pathogenic Avian Influenza Virus H5 Clade 2.3.4.4b in South America - Alfredo Bruno; Domenica de Mora; Miguel Angel Garcia-Bereguiain; Juan Cristina (Viruses)
The Highly Pathogenic Avian Influenza Virus (HPAIV) H5 clade 2.3.4.4b has caused severe outbreaks in domestic and wild birds worldwide since its emergence in 2014, and especially since 2020, with outbreaks in Europe and North America. The introduction of the virus into South America was reported for the first time in Colombia in October 2022, followed by outbreaks in other South American countries affecting poultry, wild birds, mammals, and humans. In this study, a phylogenetic and mutation analysis of the hemagglutinin (HA) gene of HPAIV H5N1 2.3.4.4b viruses isolated in South America was performed to analyze its evolution and its transmission and zoonotic potential. The analysis shows an increase in the viral effective population size between April and June 2022, which was followed by multiple outbreaks of HPAIV H5N1 clade 2.3.4.4b in South America. Moreover, the virus variants evolved from a recent common ancestor estimated to have existed in June 2017. The mean rate of evolution of the HA gene was 6.95 × 10−3 substitutions per site per year, and the sequence analysis of HA identified a mutation (D171N) located at antibody binding sites and viral oligomerization interfaces, with implications for immune response evasion and new host species infection. Additionally, viral strains from South America share the substitutions L104M, T156A, P181S, and V210A, compared to the vaccine strain A/chicken/Ghana/AVL763/2021. Understanding the dynamics of viral evolution and transmission is essential for effective prevention strategies to mitigate future outbreaks.